State-of-the-art digital watermarking attacks - Khalifa, Othman Omran; Yusof, Yusnita (IIUM Press, 2011)
Digital watermarking is a huge research area which is progressively growing. It covers theoretical studies. novel techniques, attacks and performance analysis. An embedded watermark may unintentionally or inadvel1ently be impaired by such processing. Other types of processing may be applied with the explicit goal of hindering watermark reception. In watermarking tern1inology, an "attack" is any processing that may impair detection of the watermark or communication of the information conveyed by the watermark. Broadly it can be classified as Intentional Attacks and Non-Intentional Attacks